A new rheophytic species of Syzygium (Myrtaceae) from the lower Kunene River of Angola and Namibia - Swanepoel, Wessel; de Cauwer, Vera; van Wyk, Abraham E. (Phytotaxa, 2021)
Syzygium kuneneense, here described as a new species, is known only from the northern part of the Namib Desert in the Kaokoveld Centre of Endemism, southwestern Angola and adjacent northwestern Namibia. These rheophytic shrubs or small trees grow among rocks on the floodplain and banks of the lower Kunene River on the international boundary between Angola and Namibia. Diagnostic characters for Syzygium kuneneense include the oblanceolate or narrowly elliptic leaves, dense flower heads and the pedicellate flowers. A comparison of some of the more prominent morphological features to differentiate between S. kuneneense and the morphologically most similar species, S. guineense, is provided. Based on IUCN Red List categories and criteria, a conservation assessment of Vulnerable (VU D1) is recommended for the new species.